Epigenetic regulation of drosophila germline stem cell maintenance and differentiation. - Vidaurre, V.; Chen, X. (Developmental Biology, 2021)
Gametogenesis is one of the most extreme cellular differentiation processes that takes place in Drosophila male and female germlines. This process begins at the germline stem cell, which undergoes asymmetric cell division (ACD) to produce a self-renewed daughter that preserves its stemness and a differentiating daughter cell that undergoes epigenetic and genomic changes to eventually produce haploid gametes. Research in molecular genetics and cellular biology are beginning to take advantage of the continually advancing genomic tools to understand: (1) how germ cells are able to maintain their identity throughout the adult reproductive lifetime, and (2) undergo differentiation in a balanced manner. In this review, we focus on the epigenetic mechanisms that address these two questions through their regulation of germline-soma communication to ensure germline stem cell identity and activity.